High-level dialogue deliberated solutions for gender equality and climate resilience in Africa - Wong, Madeline (CGIAR System Organization, 2022)
Climate change harms women disproportionately, exposing social and gender inequalities across the globe. At the same time, women are essential for transforming food systems that increase resilience, food and nutrition security and well-being for entire communities. That was the key message delivered at the 1st high-level dialogue on gender and climate change in Africa at the International Livestock Research Institute (ILRI) in Nairobi, Kenya, on 12 October 2022, convened by CGIAR’s Gender Equality (HER+) initiative, designed to address gender challenges in Global South food systems affected by climate change.